2017
DOI: 10.1016/j.ymgmr.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy attenuates disease progression in two Japanese siblings with mucopolysaccharidosis type VI: 10-Year follow up

Abstract: Early initiation of enzyme replacement therapy (ERT) has demonstrated clinical benefit in patients with mucopolysaccharidosis type VI (MPS VI), a progressive, multisystem autosomal recessive lysosomal disorder caused by N-acetylgalactosamine-4-sulphatase (ASB) deficiency and the consequent accumulation of glycosaminoglycan. A previous case report highlighted that 3 years of ERT with recombinant human ASB (galsulfase) was well tolerated and effective in two Japanese siblings with MPS VI who initiated ERT at 5.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
2
32
0
1
Order By: Relevance
“…Our study is consistent with the results of other clinical studies, showing acceptable compliance and an acceptable safety profile [23,26,33,34].…”
Section: Safety and Compliancesupporting
confidence: 92%
See 1 more Smart Citation
“…Our study is consistent with the results of other clinical studies, showing acceptable compliance and an acceptable safety profile [23,26,33,34].…”
Section: Safety and Compliancesupporting
confidence: 92%
“…Clinical trials show that ERT can improve quality of life and clinical and physical function, although eventually in the longterm, improvement reaches a plateau [20,21]. Overall, the current literature supports the safety and efficacy of ERT [22], especially when started at a young age [23][24][25][26].…”
Section: Introductionmentioning
confidence: 67%
“…The hearing function and the cognitive development remained stable after treatment . The other outcomes related to cardiac function, visual acuity, sleep apnea, and the size of the liver and spleen presented inconclusive results (Table ).…”
Section: Clinical Outcomesmentioning
confidence: 98%
“…A series of impressive clinical observations in siblings treated at different ages showed that ERT is reasonably able to modify the clinical course of the disease if administered at an early age [142,143,[176][177][178][179][180][181]. These case studies are only observations and not blind placebo-control studies, but they are relevant enough because they all go in the same direction.…”
Section: Ert In Siblingsmentioning
confidence: 99%